Gasto p??blico dos Estados brasileiros: uma an??lise da efici??ncia dos gastos p??s Plano Real - Vieira Neto, Francisco Gomes (2016)
This study evaluates the impact of the components of public spending on the Product growth, for the Brazilian states between 1994-2006, using a model AK of endogenous growth with 3 arguments, where it is assumed as given the stock of private capital and divides public spending into two types: a productive, ????1, and another unproductive, ????2. From this modeling, the pubic expenditure was divided according to its classification (Current expenditures and capital expenditures) and according to the four main Functional categories (health, education, defense, transport and communication), and was Estimating a fixed-effects model (linear and non-linear) with a robust estimator to see the capacity of each component to influence the per capita growth rate of the economy. The results suggest that current expenditures have a economic growth, while capital expenditures have the relation. Expenditures on health, education, transportation and communication positive relationships in relation to economic growth, although it is observed the "size effect" in these variables when linear.